Ghrelin attenuates the growth of HO-8910 ovarian cancer cells through the ERK pathway - R.X. Bai; W.P. Wang; P.W. Zhao; C.B. Li (Brazilian Journal of Medical and Biological Research, 2016)
Ovarian cancer is one of the most common causes of death from gynecologic tumors and is an important public health issue. Ghrelin is a recently discovered bioactive peptide that acts as a natural endogenous ligand of the growth hormone secretagogue receptor (GHSR). Several studies have identified the protective effects of ghrelin on the mammalian reproductive system. However, little research has been done on the effects of ghrelin on ovarian cancer cells, and the underlying mechanisms of these effects. We sought to understand the potential involvement of mitogen-activated protein kinases (MAPKs) in ghrelin-mediated inhibition of growth of the ovarian line HO-8910. We applied different concentrations of ghrelin and an inhibitor of the ghrelin receptor (D-Lys3-GHRP-6) to HO-8910 cells and observed the growth rate of cells and changes in phosphorylation of the MAPKs ERK1/2, JNK and p38. We discovered that ghrelin-induced apoptosis of HO-8910 cells was though phosphorylated ERK1/2, and that this phosphorylation (as well as p90rsk phosphorylation) was mediated by the GHSR. The ERK1/2 pathway is known to play an essential part in the ghrelin-mediated apoptosis of HO-8910 cells. Hence, our study suggests that ghrelin inhibits the growth of HO-8910 cells primarily through the GHSR/ERK pathway.